Project Obesity Zero – Influence of sleep duration, physical activity and sedentary behaviours on school age children - Vasconcelos, Marta (2012)
Introduction: Childhood obesity is considered by World Health Organization a serious public health concern. Sedentary behaviours, low levels of physical activity and changes in sleep patterns are associated with childhood obesity. The aim of this study is to evaluate the association between sleep duration, physical activity and sedentary behaviours on the nutritional status of school age children that have participated in Project Obesity Zero (POZ). Methods: POZ is a quasi-experimental, multicentric study, developed in 2009 in 5 municipalities of Portugal (Beja, Cascais, Mealhada, Melgaço and Silves) articulated with Healthcare Centres and local governments. The programme offered, to children and their families, a four stages intervention: 1) Sessions of Individual Nutrition Counselling, 2) Healthy Cooking Workshop, 3) Children’s Group Sessions and 4) Parents/families Group Counselling. The criteria used to define nutritional status of children were the CDC Growth charts (2000). This criteria was adopted by the Portuguese Ministry of Health. The information about sleep duration, physical activity and sedentary behaviours was collected from the Questionnaire about food habits, food behaviours and nutrition knowledge directed to families. Descriptive analyses were evaluated. Differences between groups were tested using chi-square test. The mean value between two dependent samples was calculated using t-test. A P-value<0,05 level was considered statistically significant. Results: From the 293 children evaluated, 152 were female (52%) and 141 (48%) were male; 9,2% had normal weight, 37,9% were overweight and 52,9% were obese. 80,4% of the children decreased their BMI percentile and Mealhada was the municipality with the greater reduction (92,0%). 95,8% of the children engaged in more than 3 days per week in a sports club reduced their BMI percentile. 83,1% of the children who slept ten hours or more per day during the weekend decreased their BMI percentile. There was an improvement in sedentary behaviors during the weekdays with a greater proportion of children spending less than two hours a day using the televison and/or the computer (64,2% in the 1st individual counselling session to 96,4% in the 4th individual counselling session). Conclusion: This study adds evidence to the eficacy of community-based projects on the prevention of childhood obesity, enphatizing the importance of the sleep duration since it’s associated with a reduction in children’s BMI percentile.